Learning Effectiveness Assessment between Primary School Students and Adults in Basic Life Support Education. (24th February 2021) - Wang, Ming-Fang; Wu, Yi-Kan; Chien, Cheng-Yu; Tsai, Li-Heng; Chen, Chen-Bin; Seak, Chen-June; Lin, Chi-Chun; Huang, Chien-Hsiung; Chaou, Chung-Hsien; Tseng, Hsiao-Jung; Ng, Chip-Jin
Abstract : Background . Out-of-hospital cardiac arrest (OHCA) remains a big issue of critical care. It is well known that bystander cardiopulmonary resuscitation (CPR) with an automated external defibrillator (AED) used did improve the survival rate. Therefore, CPR education including basic life support (BLS) and AED has been advocated for years. It showed significant improvement of knowledge and willingness to perform CPR through adolescents after the course. However, little is known regarding the ability and learning effectiveness of school students who attend such courses. Therefore, this study aimed to evaluate the CPR effectiveness of both adolescents (12 years old) and adults who undergo the same course of BLS and AED. Methods . This is a retrospective study. Sixth-grade elementary school students in Northern Taiwan were selected to compare with the adult group. Both took 90 minutes of the BLS and AED course by the doctor with BLS instructor qualification. The primary outcomes were CPR quality and passing or failing the skill examination parameters. The secondary outcome was the posttraining written test and questionnaire of CPR willingness. Results . In the written test, there was a statistical difference in the pretest score except AED knowledge, but no difference was revealed in the posttest score. No statistical difference in CPR quality was noted. In the skill examination, only checking breathing status had statistical difference (elementary group (71%) vs. adult group (86%) (p = 0.003 )). Conclusion . We revealed that sixth-grade elementary students' performance in CPR and AED was similar to that of adults after completing the current 90-minute course. Therefore, we strongly advocate offering CPR and AED courses to 12-year-old children, and these courses should emphasize checking the victim's breathing status.